The Activation of Plasminogen by Urokinase (in Comparison with Previous Observations Made with Streptokinase) - Beller, F. K; Glas, P (Thrombosis and Haemostasis, 1961)
The plasminogen activation using urokinase was studied by means of a two-phase method, the activation mixture being composed by either plasma (undiluted or diluted) and urokinase, or plasma (undiluted or diluted), urokinase and bovine or human fibrinogen (= fibrinogenolytic system).The results were compared with previous observations made with streptokinase under the same assay conditions.1. Urokinase activity was affected by the inhibitory power of undiluted plasma. By depressing the plasma inhibitors through dilution of plasma, an increase in activity was obtained.The simultaneous dilution of plasma-proactivator could be neglected, because urokinase is known to act directly on plasminogen.It seems likely that hereby the plasminogen-inhibitor-complex is dissociated in favour of plasminogen.If, contrary, the activation was carried out by streptokinase, dilution of plasma resulted in a diminution of the plasma-proactivator with consequent decrease in activity.2. Inhibition of coagulation was shown to occur in both systems, just as an initial hypercoagulability, the absence of alteration of the other clotting factors, and the failure to demonstrate an inhibitory agent as the cause of incoagulability. Respectively, the so-called “para-coagulation” was found to be only obtained if the addition of protamine sulphate to the incoagulable text mixture has been preceded by the addition of thrombin.Discussing the different activation mechanisms, we feel inclined to conclude that it may be more suitable in the estimation of fibrinolytic activity to develop — possibly on the base of our experiments — an assay system using urokinase as the activator, especially if the inhibitory agents are to be determined.